Prolonged abdominal pregnancy incidentally discovered during cesarean section: a case report - Hamidou Soumana Diaouga; Maimouna Chaibou Yacouba; Tidjani Mahamat Hissen; Maina Oumara; Inoussa Daouda Bako; Rahamatou Madeleine Garba; Nafiou Idi; Madi Nayama (BMC, 2024)
Abstract Background Abdominal pregnancy is a rare medical condition that is still missed in developing countries due to inadequate medical facilities. The clinical indicators manifest in various forms and are nonspecific, making it challenging to diagnose and often leading to delayed detection. However, obstetric ultrasound serves as an essential tool in early detection. Our objective was to share our experience dealing with this condition and emphasise the importance of early ultrasound diagnosis through efficient pregnancy monitoring in our regions. Case presentation 35-year-old Black African woman who had ten months of amenorrhea sought consultation due to an absence of active foetal movements. Her pregnancy was of 39 weeks with fetal demise which was confirmed following clinical examination and ultrasound. She underwent cesarean section in view of transverse position of fetus. During cesarean section, the fetus was found within the abdominal cavity with the placenta attached over the left iliac fossa including surface of left ovary. The uterus and right adnexa were within normal limits. A 2600 g macerated fetus with placenta and membranes were extracted without any complications. The maternal outcome was successful. Conclusions Abdominal pregnancy remained an inadequately diagnosed condition in developing countries. It is imperative to increase awareness among pregnant women regarding high-quality prenatal care, including early obstetric ultrasound, from conception. Meanwhile, healthcare professionals should receive continuous training and the technical platform modernised. To ensure accurate diagnosis, the location of the gestational sac must be identified for every pregnant woman during their initial ultrasound appointment.